If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -42 = -6(1 + -3x) -42 = (1 * -6 + -3x * -6) -42 = (-6 + 18x) Solving -42 = -6 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. -42 + -18x = -6 + 18x + -18x Combine like terms: 18x + -18x = 0 -42 + -18x = -6 + 0 -42 + -18x = -6 Add '42' to each side of the equation. -42 + 42 + -18x = -6 + 42 Combine like terms: -42 + 42 = 0 0 + -18x = -6 + 42 -18x = -6 + 42 Combine like terms: -6 + 42 = 36 -18x = 36 Divide each side by '-18'. x = -2 Simplifying x = -2
| (x+18)*2=4x-12 | | 1+3x+94=180 | | 1/8-y/9=1/72 | | -2m+5=14+m | | 36-7c=22 | | -5r-8=-5r-16 | | 5x^2=170 | | 5x+6y=9y+1 | | 1-5/6-1/12 | | 9z-2m+2-3= | | 10=n-8+2n | | 1+5n=10 | | 46+3x+2x-1=180 | | 2.7-1.9= | | (160-2y)/3*y=1000 | | x=y(0.8) | | -0= | | n+98=116 | | 8(m-5)+3=6m+14-6m+13 | | 12p^2-48p-60=0 | | x+x+x+x+x=5x | | 0.125(c+230)=200 | | 6x/500=600 | | -2(t+2)+5t=6t-11 | | Y^2-80y+500=0 | | 2(n+2)=12 | | 2d+8=2d+28+10 | | -15x=-5(3x+7)5(3x+7) | | 8x^3-2x^7=0 | | 4+7(3m)= | | -6+8x=10 | | 3(2k+12)=-42 |